PERCEPTIONS OF MARGINALIZED PEOPLE ON BIRTH RATE CONTROL - Ahmad Syaekhu; Hamsu Abdul Gani; Ramli Umar; Irma Irma (International Conference on Social and Islamic Studies, 2021)
The government's efforts to control population growth can be seen from their support for relevant agencies to improve birth control. Fertility is the main component of population growth is closely related to infant mortality, education levels and the economy. In 2019, Indonesia's total fertility rate is still at 2.2 per woman, the target is 2.1 per woman to create a prosperous family. The Covid-19 pandemic condition that forced changes in all lines of life, including the PSBB policy by the government, triggered an explosion in the birth rate. This is further exacerbated by the decline in the use of contraceptives. Contraceptive implants decreased from 81,062 to 51,536, injectables from 524,989 to 341,109, birth control pills from 251,619 to 146,767, condoms from 31,502 to 19,583, MOP (vasectomy) from 2,283 to 1,196, and MOW (tubectomies) from 13,571 8,093. Public knowledge of contraceptives, and the choice of long-term contraception can optimize birth control. Therefore, this research is focused on looking at the perception of marginalized people in Makassar City on birth control. This research is an analytic survey with four knowledge indicators used, namely birth control, prosperous family, risk of early marriage and long-term method. The survey results show that 95.6% of the population understand well about controlling the birth rate, 97.8% are good for prosperous families, and 100% are good for long-term contraception. The analysis test proved that the understanding of birth rate control, prosperous family and long-term contraceptive method had a significant relationship with each p value = 0.00<0.05.